2003
DOI: 10.1080/02701367.2003.10609067
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Sexual Harassment and Abuse among Norwegian Elite Female Athletes and Nonathletes

Abstract: This paper compares the prevalence of sexual harassment and abuse among 660 Norwegian elite female athletes and an age-matched control sample of nonathletes. It also explores differences in the prevalence of harassment and abuse in sport and work or school settings and compares harassment and abuse perpetrated by male authority figures and peers in these different contexts. No differences were found between the athletes and controls in overall prevalence of sexual harassment or abuse. However, the athletes exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(80 citation statements)
references
References 23 publications
6
67
2
5
Order By: Relevance
“…Indeed, while one study report a rate as low as 3% (Décamps et al, 2009), another reported a much higher rate of 52% (Fasting, Brackenridge, & Sundgot-Borgen, 2004). The study populations could explain these variations.…”
Section: Sexual Harassment By a Coachmentioning
confidence: 82%
See 2 more Smart Citations
“…Indeed, while one study report a rate as low as 3% (Décamps et al, 2009), another reported a much higher rate of 52% (Fasting, Brackenridge, & Sundgot-Borgen, 2004). The study populations could explain these variations.…”
Section: Sexual Harassment By a Coachmentioning
confidence: 82%
“…: Chroni & Fasting, 2009;Fasting et al, 2014;Vanden Auweele et al, 2008), while a few others also included male athletes (Alexander and al., 2011;Décamps et al, 2009). Décamps et al (2009) have shown that 3.4% of boys whereas 4.3% of girls were sexually harassed. This difference was non significant according to the authors, which suggests that boys may experience as much sexual harassment in sport as girls.…”
Section: Sexual Harassment By a Coachmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not studied extensively, it has also been suggested that participation in sports may protect females from victimization in that it develops strength and self-esteem (Fasting, Brackenridge, & Sungot-Borgen, 2003). An often held assumption is that fraternity and sports membership are significant correlates for perpetrating sexually aggressive acts, largely due to hyper masculine beliefs, secrecy, and peer pressure (Boeringer, 1996;Martin & Hummer, 1989).…”
Section: College Life and Risk Factors For Victimizationmentioning
confidence: 99%
“…Previous research has indicated that the experiences of sexual harassment can be associated with the masculine culture of sport, and should therefore be explained by more structural conditions like unbalanced power distribution [27]. This does not mean that all coaches are harassing coaches, yet studies that have explored the experiences of sexual harassment among female athletes indicate that the coach is often the perpetrator [28][29][30][31][32][33]. Furthermore, studies of the experiences of sexual harassment in sport settings have indicated that the perpetrator usually is a man [28,34].…”
Section: Introductionmentioning
confidence: 99%